Bravehearts of Bharat : vignettes from Indian history [EBOOK] - Sampath, Vikram (Gugugram, Haryana, India : Penguin/Viking, an imprint of Penguin Random House, 2022)
Exploring the lives, times and works of the fifteen long-forgotten and mostly neglected unsung heroes and heroines of our past, this book brings to light the contribution of the warriors who not only donned armour and burst forth into the battlefield but also kept the flame of hope alive under adverse circumstances. Narrating the tales of valour and success that India, as a nation and civilization, has borne witness to in its long and tumultuous past, the book opens a window to the stories of select men and women who valiantly fought against invaders for their rights, faith and freedom.
Lalitaditya Muktapida of Kashmir -- Rajaraja Chola and Rajendra Chola -- Rani Naiki Devi of Gujarat -- Rani Rudrama Devi of Warangal -- Maharana Kumbha of Mewar -- Rani Abbakka Chowta of Ullal -- Chand Bibi of Ahmednagar -- Lachit Barphukan of Assam -- Kanhoji Angre -- Banda Singh Bahadur -- Martanda Varma of Travancore -- Devi Ahilya Bai Holkar of Indore -- Rajarshi Bhagyachandra Jai Singh of Manipur -- Velu Nachiyar of Sivaganga -- Begum Hazrat Mahal of Awadh.
Includes bibliographical references (pages 327-334) and index.
Keywords: India -- History; India; Biographies; History; Biographies